Massage Therapy Prenatal sebagai Intervensi Mengurangi Kecemasan pada Ibu Primigravida di Wilayah Kerja Puskesmas Bangkinang Kota, Provinsi Riau - Apriza Apriza; Erlinawati Erlinawati; Dewi Anggriani Harahap (Jurnal Sehat Mandiri, 2024)
The unpreparedness of pregnant women in dealing with changes in pregnancy often causes stress and anxiety. Anxiety experienced by pregnant women has a negative impact on the health of the mother and fetus. The results of a survey of pregnant women at the Bangkinang Kota Health Center, many pregnant women experience anxiety due to psychological factors. The purpose of this study was to determine the effectiveness of Prenatal Massage Therapy in reducing anxiety experienced by primigravida pregnant women. Methodology: Quasy experiment with one group pretest-posttest design. Participants were 30 pregnant women. Data were collected by assessing the anxiety level using the HARS measurement tool and independent T test analysis. Results showed that the average anxiety level of pregnant women before massage therapy was 2.60 and the average level of anxiety for pregnant women after massage therapy was 0,90. The average difference between the anxiety of primigravida pregnant women before and after massage therapy was 1.7 with a SD of 0.466. The statistical test results obtained a p-value of 0.000. There is a significant difference in the average between primigravida pregnant women anxiety before and after receiving massage therapy. Conclusions: Massage therapy is recommended as an intervention to reduce anxiety in pregnant women. It is recommended for health workers to apply prenatal massage therapy as an alternative to reduce anxiety in pregnant women.